EVALUASI PROGRAM TRANSMIGRASI (STUDI KASUS PROGRAM TRANSMIGRASI DI DISTRIK KURIK, MUTING DAN SEMANGGA KABUPATEN MERAUKE - Rinno Bahari Adi Pradana (SOCIETAS, 2018)
This study aims to describe the transmigration program evaluation in Merauke. To get the data of the study, researchers interviewed 11 informant Data analysis using the method of qualitative analysis, this study used a descriptive approach with qualitative methods. The research found that the transmigration program in Merauke runs according to the purpose of transmigration i.e. equitable population, leveling construction, as well as boost the economy of the community trans or local communities. But there are still some areas that are still lags behind resettlement in the area due to its geographical conditions other resettlement, transmigration program overall in Merauke has succeeded in the development of the region, as well as the successful to improve the perkonomian of the society and some areas of transmigration has developed into the center of the new economy and became the new administrative region. The findings in the field indicates that there are other factors that also helped the success of the transmigration program, namely the existence of crosscutting activities of the economy so that the economy of the society can be increased when viewed from before the transmigration until after the resettlement. Keywords: evaluation, the transmigration Program.